2014
DOI: 10.1063/1.4894792
|View full text |Cite
|
Sign up to set email alerts
|

Volume phase transition of polyelectrolyte gels: Effects of ionic size

Abstract: Although the volume transition of the polyelectrolyte gel has been studied for decades, little research on the effects of size of the mobile ions has been conducted. In the present paper, Tanaka's classical theory of polyelectrolyte gel is extended to the cases of mobile ions of finite volume. In the salt free limit, the theoretical results show that the discontinuous volume transition of the polyelectrolyte gel will become a continuous one with an increase of the counterionic size. An increase in salt concent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Specific ion effects are ubiquitous in chemistry and biology. Previous studies have demonstrated that ion-specific effects, reflected by factors such as sizes and valences of ions, have a great influence on the phase behaviors of different types of PE systems. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific ion effects are ubiquitous in chemistry and biology. Previous studies have demonstrated that ion-specific effects, reflected by factors such as sizes and valences of ions, have a great influence on the phase behaviors of different types of PE systems. …”
Section: Introductionmentioning
confidence: 99%
“…Properties of PEs, including swelling, conductivity, viscosity, correlation length, structure, etc., can be tuned through adjusting the counterionic size in both aqueous and various polar media. For example, Bodrova and Potemkin concluded that the counterionic size influences both the character of swelling-to-collapse transition of the PE gel and the fraction of ion pairs through a theoretical study . Kramarenko group studied the effects of counterionic size on the PE gel using experiments combined with theoretical calculations .…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical works by Bodrova and Potemkin and by Muthukumar’s group, also devoted to counterion specificity in polymer gel swelling and considering possible ion pairing, have either examined weakly charged PE gels or neglected Manning condensation at high f . Another publication has focused solely on steric counterion impact on a gel swelling at low degrees of gel ionization entirely avoiding possible ion association. DPD computer simulations of a single highly charged chain have shown that not only counterion size but also the charge location (in the center of counterion or on its surface) defines chain dimensions as well as the region of collapsed ionomer state stability and even multiplet structure in it .…”
Section: Introductionmentioning
confidence: 99%
“…However, the theory developed for the case of relatively low content of ionic groups (f < 0.3) is unable to explain (i) absence of gel swelling or even slight gel contraction at f exceeding 0.5 and (ii) certain discrepancy of swollen gel volumes with TMA + , TEA + , and TBA + counterions in the region of high f. The former effect has been earlier observed experimentally not merely in pure methanol but also in water−methanol mixtures and pure water for gels of sodium salt of PAA 14 as well as in water for partially quaternized PVP gel. 30 Theoretical works by Bodrova and Potemkin 36 and by Muthukumar's group, 15 also devoted to counterion specificity in polymer gel swelling and considering possible ion pairing, have either examined weakly charged PE gels or neglected Manning condensation at high f. Another publication 37 has focused solely on steric counterion impact on a gel swelling at low degrees of gel ionization entirely avoiding possible ion association. DPD computer simulations of a single highly charged chain have shown that not only counterion size but also the charge location (in the center of counterion or on its surface) defines chain dimensions as well as the region of collapsed ionomer state stability and even multiplet structure in it.…”
Section: Introductionmentioning
confidence: 99%